THE DEMAND FOR LABOR MARKET OF URBAN INFORMATICS AND RAILWAY SYSTEMS GRADUATE PROGRAMS - Petlaor, Nuttapong; Tiyawongsuwan, Sarit; Thirakultomorn, Tinn; Srisilp, Pantiwa; Khotsing, Thannaphat (Journal of MCU Phetchaburi Review, 2022)
The aim of this research was to study and analyze the demand for graduate labor market of Urban Informatics and Railway Systems graduate program, as well to suggest the characteristics of the graduates in accordance with the needs of employer. It was a survey research using quantitative data collection methods as main. The target groups consisted of entrepreneurs, executives, and employees in various sectors across the country of 120 people. The results revealed as follows. Most of the reason for labor demand was to recoup workers who resigned (35.0%). The most needed occupation type was Urban Informatics/Urban Planning (51.7%). The bachelor's degree (65.0%), GPA 2.5 (45.0%), 0-2 years of work experience (48.3%), and aged range with 26-35 years old (64.2%) was most required. Most of the employer was not specified gender of labor (70.8%). The employment that most employer wanted was paying salary with 15,000 – 20,000 baht (45.0%) and being a full-time job (84.2%). The property of labor to be desired were responsibility (97.6%), proficiency in English (72.5%), and ability to use Microsoft Office computer programs (95.0%). Important recommendations for develop the graduate’s program were emphasizing on graduates to be able to think, analyze, integrate and apply knowledge gained for using in actual work appropriately with the city's public policy.